When case reporting becomes untenable: Can sewer networks tell us where COVID-19 transmission occurs?. (1st February 2023) - Wang, Yuke; Liu, Pengbo; VanTassell, Jamie; Hilton, Stephen P.; Guo, Lizheng; Sablon, Orlando; Wolfe, Marlene; Freeman, Lorenzo; Rose, Wayne; Holt, Carl; Browning, Mikita; Bryan, Michael; et al.
Abstract: Monitoring SARS-CoV-2 in wastewater is a valuable approach to track COVID-19 transmission. Designing wastewater surveillance (WWS) with representative sampling sites and quantifiable results requires knowledge of the sewerage system and virus fate and transport. We developed a multi-level WWS system to track COVID-19 in Atlanta using an adaptive nested sampling strategy. From March 2021 to April 2022, 868 wastewater samples were collected from influent lines to wastewater treatment facilities and upstream community manholes. Variations in SARS-CoV-2 concentrations in influent line samples preceded similar variations in numbers of reported COVID-19 cases in the corresponding catchment areas. Community sites under nested sampling represented mutually-exclusive catchment areas. Community sites with high SARS-CoV-2 detection rates in wastewater covered high COVID-19 incidence areas, and adaptive sampling enabled identification and tracing of COVID-19 hotspots. This study demonstrates how a well-designed WWS provides actionable information including early warning of surges in cases and identification of disease hotspots. Graphical abstract: Highlights: The performance of WWS for infectious disease depends critically on sampling design. Knowledge of the sewer network helps in design of optimal sampling strategies. The proposed adaptive nested WWS sampling enables tracing of COVID-19 hotspots. Nearly 900 wastewater samples were collected at influent lines and community manholes. The collected data provides actionable information to guide public health response.